EVALUASI HUBUNGAN KENAIKAN PUTARAN MESIN TERHADAP KEBISINGAN PADA RUANG KEMUDI MOBIL TOYOTA RUSH 1.5 - Siagian, Tony (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2024)
The effect of machine movement will generate mechanical vibrations and these mechanical vibrations will cause vibration propagation in the air and this will create noise. This noise itself in situations that exceed the threshold will cause discomfort to driver and can have an impact on health. In this research, it was obtained by increasing the engine speed starting from 1000 rpm and increasing at intervals of 200 rpm up to the maximum speed at the position of 2800 rpm. Found that the noise level was obtained from the lowest position of 48 dB which then increased at intervals of 1 - 2 dB up to the maximum position with a noise level of 62 dB. From these two measuring parameters, the level of correlation coefficient between the increase in engine speed and the increase in noise level, rxy = 0.9220, found that a strong positive correlation between these two measuring parameters. With the noise level in the car driving room ranging from 48 – 62 dB, referring to the Minister of Environment (LHK) Regulation No. 7/2009 concerning motor vehicle noise thresholds, the maximum quality standard set is 77 decible (dB) for passenger cars, so the level The noise that arises in the driver's cabin of the car is still in a safe condition for the driver and passengers in the car